2011
DOI: 10.2174/1876528901104010064
|View full text |Cite
|
Sign up to set email alerts
|

The Chemokine SDF1/CXCL12: A Novel Autocrine/Paracrine Factor Involved In Pituitary Adenoma Development

Abstract: Abstract:The relevance of the chemokine/chemokine receptor system has broaden to several tissues. Besides their physiologic role as chemotactic cytokines in immune surveillance, it is now clear that chemokines are key players in several pathological processes such as inflammation, infection, and cancer. In particular the altered expression of SDF1/CXCL12 and its receptor CXCR4 strongly affects cancer cell proliferation, recruitment of immunosuppressive cells, neovascularization and metastasization. CXCL12 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 132 publications
1
11
0
Order By: Relevance
“…In vitro studies showed that CXCL12 activation provided a proliferation advantage to the adenoma cells [74]. CXCR4 was also expressed in several stem cell populations [78] including stem/progenitors involved in pituitary development [71], we hypothesized that putative CSCs for human pituitary adenomas may derive from CXCL12/CXCR4-expressing cells in the normal pituitary, and thus this phenotype was extended to all the adenoma cells [79]. In particular, these data suggested that, due to the proliferative advantage granted by CXCR4 constitutive activation, these cells could be one of the target cell populations that clonally expand during pituitary tumorigenesis.…”
Section: Pituitary Adenoma Stem Cellsmentioning
confidence: 99%
“…In vitro studies showed that CXCL12 activation provided a proliferation advantage to the adenoma cells [74]. CXCR4 was also expressed in several stem cell populations [78] including stem/progenitors involved in pituitary development [71], we hypothesized that putative CSCs for human pituitary adenomas may derive from CXCL12/CXCR4-expressing cells in the normal pituitary, and thus this phenotype was extended to all the adenoma cells [79]. In particular, these data suggested that, due to the proliferative advantage granted by CXCR4 constitutive activation, these cells could be one of the target cell populations that clonally expand during pituitary tumorigenesis.…”
Section: Pituitary Adenoma Stem Cellsmentioning
confidence: 99%
“…CXCR4 is upregulated in putative PSCs (44,52), and SP cells of mouse pituitary gland (34). In the stem cell niches CXCL12/CXCR4 axis acts as chemoattractant and trophic factor for several cell types via paracrine and/or autocrine mechanisms (55), and induces EMT in progenitors (47,56); this activity was also described in pituitary (51), further suggesting an association between its expression/activity and the stem cell phenotype.…”
Section: Pituitary Stem Cells In Cell Turnover and Responses To Hormonesmentioning
confidence: 98%
“…Moreover, in vitro studies showed that CXCL12 activation is a mitogen for human pituitary adenoma cells [ 67 ]. Thus, it was proposed that putative CSCs for human pituitary adenomas may derive from CXCR4 + /CXCL12 + cells in normal pituitary and that, due to the proliferative advantage granted by the autocrine activation of CXCR4 via the constitutive CXCL12 secretion, these cells could be one of the cell populations that clonally expand during pituitary tumorigenesis [ 68 ].…”
Section: Adult Pituitary Stem Cells and Tumor Developmentmentioning
confidence: 99%